2018
DOI: 10.1007/s00262-018-2282-1
|View full text |Cite
|
Sign up to set email alerts
|

A secreted PD-L1 splice variant that covalently dimerizes and mediates immunosuppression

Abstract: Targeting immune checkpoint pathways, such as programmed death ligand-1 (PD-L1, also known as CD274 or B7-H1) or its receptor programmed cell death-1 (PD-1) has shown improved survival for patients with numerous types of cancers, not limited to lung cancer, melanoma, renal cell carcinoma, and Hodgkin lymphoma. PD-L1 is a co-inhibitory molecule whose expression on the surface of tumor cells is associated with worse prognosis in many tumors. Here we describe a splice variant (secPD-L1) that does not splice into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
104
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(113 citation statements)
references
References 35 publications
7
104
1
1
Order By: Relevance
“…published secreted PD-L1 splice variants. 22 While we observed that PD-L1 is also shed from the surface of extracellular vesicles, further work is required to determine the relative contribution of exosome-derived sPD-L1 to resistance. It is also uncertain whether removal of either ADAM10 or ADAM17 alone, as in our siRNA studies but not in our peptide and antibody inhibitor experiments, is sufficient to rescue PD-(L)1 inhibitor sensitivity.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…published secreted PD-L1 splice variants. 22 While we observed that PD-L1 is also shed from the surface of extracellular vesicles, further work is required to determine the relative contribution of exosome-derived sPD-L1 to resistance. It is also uncertain whether removal of either ADAM10 or ADAM17 alone, as in our siRNA studies but not in our peptide and antibody inhibitor experiments, is sufficient to rescue PD-(L)1 inhibitor sensitivity.…”
Section: Discussionmentioning
confidence: 78%
“…The source of soluble PD-L1 is uncertain. While others have reported secreted PD-L1 splice variants, 22 we hypothesized that PD-L1 may be cleaved from the surface of tumor cells. In particular, closely related metzincin metalloproteinases ADAM10 and ADAM17 commonly cleave immune cell surface ligands.…”
Section: Resultsmentioning
confidence: 96%
“…An in vitro experiment demonstrated that a splice variant form of PD-L1 (secPD-L1) could inhibit T-cell proliferation. secPD-L1 has been detected in malignant cells but can also be considered a negative immune regulator in pregnancy complications (61). Taken together, these results suggest that the PD-1/B7-H1 checkpoint maintains the local immunological environment by interacting with different immune cells and mediating cytokine secretion.…”
Section: B7-h1 and B7-dcmentioning
confidence: 83%
“…Further interest attracts the measurement of PD-L1 (soluble and expressed in extracellular vesicles, EV) in liquid biopsies. Soluble PD-L1 is a splice variant without a transmembrane domain capable to directly inhibit T cell proliferation and IFN-γ production [94]. Elevated basal levels of soluble PD-L1 in the plasma of melanoma patients was associated with progressive disease [95].…”
Section: Predicting the Response To The Ici Therapymentioning
confidence: 99%